The idea of continuity in the philosphies of Leibniz and Peirce - Flórez Restrepo, Jorge Alejandro; Arias Cardona, Jesús Esteven (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This article offers an analysis of the concept of continuity, as it has been developed by two of its main exponents, Leibniz and Peirce. It begins defining the meaning of the concept, pointing out the different properties of the continuum identified by Leibniz and Peirce. After that, it takes into account the consequences and philosophical applications that the concept has for both philosophers, especially in their ontologies. In the first place, it exposes what Leibniz called the law of continuity and its different versions. Then, what Peirce called «synechism», which encompasses the whole set of ideas of this philosopher about continuity and its philosophical implications. Here we try to show, especially, how synechism is the key to the understanding and solving of many logical, epistemological and metaphysical problems, such as the axioms of logic, the justification of knowledge, mind body dualism, evolutionism and Realism about the universals.
Keywords: Leibniz; Peirce; continuity; law of continuity; synechism; infinite